What is News? A Young Peoples' Perspective in Kenya. Issue 4 (2nd October 2021) - Tallam, Edwin
ABSTRACT : This study investigates emerging news consumption patterns among a contingent of young people drawn from two public universities in Kenya. Guided by the relatively new concept of scalable sociality and emerging third wave of non-normative audience studies in sub-Saharan Africa, this study maps emerging news exposure avenues among young people in Kenya. Through a mixed approach, it specifically explores how young people access and consume news through internet-enabled mobile devices. It also probes how young people define news and draws a nexus between the rise of news technologies, particularly mobile phones and the shifting definition(s) of news. Findings support the conclusion that internet-enabled mobile devices continue to cause unprecedented disruption in Kenya. This has profoundly altered the understanding of news. News was mainly understood as a node that connects young people to themselves and to the social world. However, the ambivalence evident in young people's conceptualization of news is reflective of the dynamic society within which the internet and mobile devices are critical catalysts in accessing and consuming news. News consumption thus becomes a complex, multilayered process enmeshed in a web of technical and social networks online and offline.